Greek Cotton Merchants in the New Orleans Mosaic - Billinis, Alexander (The Northern Mariner / Le marin du nord, 2025)
Beneath the headlines of the mid-nineteenth century cotton trade was a well-financed network of Greek commodities merchants operating in New Orleans and New York, part of a network operating in the major ports of Europe, the Mediterranean, and India. This network played a niche role in the Southern cotton trade, and a primary role in Anglo-French efforts to develop alternative supply chains to Southern cotton during the Civil War by shipping cotton from Egypt, India, and the Ottoman Empire. The network also founded the first Orthodox church community in the United States.